2011
DOI: 10.1371/journal.pntd.0001426
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Dengue Illness and the Cost-Effectiveness of Future Vaccination Programs in Singapore

Abstract: BackgroundDengue illness causes 50–100 million infections worldwide and threatens 2.5 billion people in the tropical and subtropical regions. Little is known about the disease burden and economic impact of dengue in higher resourced countries or the cost-effectiveness of potential dengue vaccines in such settings.Methods and FindingsWe estimate the direct and indirect costs of dengue from hospitalized and ambulatory cases in Singapore. We consider inter alia the impacts of dengue on the economy using the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
142
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(151 citation statements)
references
References 44 publications
4
142
5
Order By: Relevance
“…35 We used the human capital approach to estimate these indirect costs. 36,37 Because most subjects were less than 6 years old, the cost of school days lost was negligible.…”
Section: Costsmentioning
confidence: 99%
“…35 We used the human capital approach to estimate these indirect costs. 36,37 Because most subjects were less than 6 years old, the cost of school days lost was negligible.…”
Section: Costsmentioning
confidence: 99%
“…The dengue incidence rate was 98.1/100,000 population in 2010, with a case-fatality ratio of 0.08 % [1]. Although the incidence rate was not the highest in the Asia-Pacific region, the disease had high economic impact [2]. It was estimated that the average economic impact of dengue illness in Singapore over one 10-year period from 2000 to 2009 was between US$ 0.85 billion and US$ 1.15 billion [2].…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study in Singapore concluded that a dengue vaccine involving three doses and conferring ten years of immunity would be cost-effective at a price threshold of USD 95 per dose, given Singapore GDP per capita of about USD 55,000. However, the authors admitted several limitations in the estimation of the economic and disease burdens [11]. The low efficacy and theoretical increase in risk due to vaccineinduced ADE have not been incorporated in their current pricing model.…”
Section: New Model For Dengue Pharmacoeconomicsmentioning
confidence: 99%
“…The vaccine coverage fc required to bring the basic reproduction number R0 to below 1 with a vaccine efficacy α is given as [11]:…”
Section: New Model For Dengue Pharmacoeconomicsmentioning
confidence: 99%